The Influence of Parent Brands Commitment On Consumers Atitude toward co branding between those brands - Aisyah, Azizah Nur; Nasution, Reza Ashari (Jurnal Manajemen Teknologi, 2010)
This paper examines the influence of parent brands' commitment on consumers' attitude toward cobranding. Co-branding refers to the combination of two brand names to launch a single and unique product for a short to long term cooperation. Two experiments were conducted to test the hypotheses. The 82 subjects were exposed to two sessions of experiment; evaluations on each brand with no cobranding, evaluations on co-branding. Consumers' attitude was derived through obtaining consumers' perception on brand personality and favorability. The findings showed that parent brands with high commitment received more positive attitude compared to parent brands with low commitment.Keywords: co-branding, level of commitment, brand personality